Anesthetic technique and cancer surgery outcomes. Issue 3 (June 2021) - Dubowitz, Julia; Hiller, Jonathan; Riedel, Bernhard
Abstract : Purpose of review: Surgery remains integral to treating solid cancers. However, the surgical stress response, characterized by physiologic perturbation of the adrenergic, inflammatory, and immune systems, may promote procancerous pathways. Anesthetic technique per se may attenuate/enhance these pathways and thereby could be implicated in long-term cancer outcomes. Recent findings: To date, clinical studies have predominantly been retrospective and underpowered and, thus limit meaningful conclusions. More recently, prospective studies of regional anesthesia for breast and colorectal cancer surgery have failed to demonstrate long-term cancer outcome benefit. However, based on the consistent observation of protumorigenic effects of surgical stress and that of volatile anesthesia in preclinical studies, supported by in vivo models of tumor progression and metastasis, we await robust prospective clinical studies exploring the role of propofol-based total intravenous anesthesia ( cf. inhalational volatiles). Additionally, anti-adrenergic/anti-inflammatory adjuncts, such as lidocaine, nonsteroidal anti-inflammatory drugs and the anti-adrenergic propranolol warrant ongoing research. Summary: The biologic perturbation of the perioperative period, compounded by the effects of anesthetic agents, renders patients with cancer particularly vulnerable to enhanced viability of minimal residual disease, with long-term outcome consequences. However, low level and often conflicting clinical evidence equipoise currently exists with regards to optimal oncoanesthesia techniques. Large, prospective, randomized control trials are urgently needed to inform evidence-based clinical practice guidelines.